Role of Health Awareness Campaigns in Improving Public Health:A Systematic Review: Life Sciences-Public Health - Bugshan, Waleed Mohammed; Qahtani, Saad Jarallah Al; Alwagdani, Nayel Ayidh; Alharthi, Majed Safar; Alqarni, Abdullah Mohammed; Alsuat, Hani Muteb; Alqahtani, Naif Hadi; Rabia Alqahtani, Mohammed; Thaar Alshammari, Mohammed; Albaqami, Rashed Aqeel; Almotairi, Ahmed Hammad (International Journal of Life Science and Pharma Research, 2022)
Public health is a multidisciplinary field that intervenes at organizational, community, and individual levels to prevent disease, improve quality of life, and create an environment in which people can enjoy good health. Public health campaigns are used worldwide for a variety of purposes and are based largely on psychological theories. Such theories attempt to understand the effect of many elements in human behavior that influence decisionmaking when it comes to health issues and their solutions. Health awareness campaigns are designed in the way that their role is to promote or protect health or prevent illness in communities or individuals by creating awareness. Health awareness campaigns are an essential part of public health as through health promotion and education, awareness levels of individuals can be increased leading to better adoption of preventive strategies. The aim of this research is to review the available literature about the role of health awareness campaigns in public health. Health awareness programs that include the use of different forms of communication media and the provision of health-related products are effective in changing people's attitudes and behavior. Through behavioral modification, health communication can reduce mortality and morbidity, thus reducing disease burden. During the current digital era, health awareness and communication can be easily conducted on mass media platforms. Health awareness campaigns tend to increase the knowledge and awareness levels of individuals and communities. This is supported by current literature, however, more research in the future can help us better understand the role of health awareness campaigns in the field of public health.